Fluid-dynamic model of hydrocarbon accumulation in salt-strike-slip structures of the Dnieper-Donetsk depression - Василенко, О. Л. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
The article examines the problems of Geology and petroleum potential of a new type in the tectonic structures of salt-strike-slip structures (SSSS), established by the author in the Dnieper-Donetsk depression (DDD). Depending on geodynamic conditions strike-slip within the salt dome shaft are formed of a convergence (compression) and divergence (stretching) zone. Inside these zones areas of transtension and transgression are allocated. These sections meet five morphogenetic types of salt-strike-slip structures: Chutivsky, Vesnyansky, East-Medvedovsky, Melikhovskay and Kochubeevsky. Developed a fluid dynamic spatial model of hydrocarbon accumulations formation in SSSS allows to predict migration paths of hydrocarbons and allocate traps in natural reservoirs. In the formations of deposits in SSSS a decisive influence have the processes of horizontal compression and horizontal strike-slip. These processes are the basis for fluid-dynamic models of hydrocarbon deposits based on the structural features of SSSS. It covers: 1) the formation of decomposition zones as the source and useful volume for accumulation of hydrocarbons; 2) following upward vertical migration of fluid flows of loosened zones on plots of shear tectonic dislocations; 3) the formation of hydrocarbon traps under reliable salt confining beds. The important factor in the localization of hydrocarbons in the SSSS is a complex tectonic dislocation where a significant role is played by areas of ancient deep faults, which are channels for the fluid heat and mass transfer. It is established that traditional gas condensate field is characterized by: a secondary reservoirs of fractured-porous type; component two-phase (gas-condensate); united gas-water contact controlling massive sheet deposit; maximum overpressure in the roof deposits under salt lid and anticlinal, mass of reservoir traps. In fields dedicated to SSSS, characteristics of oil and gas are: a wide range of reservoir types with depth; a wide range of phase state of hydrocarbons; absence of a common gas-water contact; multilayered type deposits; the absence of abnormally high reservoir pressure peaks; reservoir types in combined non-anticlinal traps.